2012
DOI: 10.1021/ct300546c
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Container: Complexes of C50H10with Small Molecules

Abstract: The stability of complexes of a recently synthetized (Scott et al. J. Am. Chem. Soc.2011, 134, 107) opened nanocontainer C50H10 with several guest molecules, H2, N2, CO, HCN, H2O, CO2, CS2, H2S, C2H2, NH3, CH4, CH3CN, CH3OH, CH3CCH, 2-butyne, methyl halides, and with noble gas atoms, has been examined by means of symmetry-adapted perturbation theory of intermolecular interactions, which fully incorporates all important energy components, including a difficult dispersion term. All complexes under scrutiny have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 86 publications
0
15
1
Order By: Relevance
“…145 Still, SAPT generally remains more costly than variational EDAs and visualization tools (vide infra). The work to improve efficiency has produced the aforementioned XSAPT 116,146 as well as linear-scaling SAPT, 147 but these approaches use modified or semiempirical dispersion expressions.…”
Section: Applying Pt-based Edasmentioning
confidence: 99%
“…145 Still, SAPT generally remains more costly than variational EDAs and visualization tools (vide infra). The work to improve efficiency has produced the aforementioned XSAPT 116,146 as well as linear-scaling SAPT, 147 but these approaches use modified or semiempirical dispersion expressions.…”
Section: Applying Pt-based Edasmentioning
confidence: 99%
“…29 The present study of chiral recognition by a fullerene cage was carried out as a continuation of our calculations on endohedral fullerene complexes. [30][31][32][33] We have shown that C 60 can host only one hydrogen molecule whereas for C 70 we demonstrated the possible existence of both complexes with one or two H 2 guests, 34 the calculated energy difference between them, partly accidentally, was equal to a later determined experimental result. 35 One of the present authors (HD) postulated as early as in 2001 that for applications of endohedral fullerene complexes, efficient synthetic and purification procedures for higher fullerenes are needed.…”
Section: Introductionmentioning
confidence: 55%
“…The interaction energy was calculated either by the supermolecular (DFT, MP2) or by the perturbational approach. In previous studies, [31][32][33] eqn (1) was utilized with the three energies calculated by either DFT using the B97D or PBE + D3(BJ) functional, 66,67 MP2, or the spin-component-scaled MP2 (SCS-MP2). 68 For all supermolecular calculations, the Boys-Bernardi counterpoise scheme 69 was applied in order to reduce the basis-set superposition errors (BSSE), i.e.…”
Section: Methodsmentioning
confidence: 99%
“…59 In addition to having high structural perfection, exceptional electronic, mechanical, optical, thermal, and transport properties, the hollow spaces within the cylindrical structures could be employed for a plethora of purposes in molecular encapsulation such as gas storage and drug delivery. 1013 The current work is motivated by recent developments in CNT research, wherein CNTs are shown to act as novel porous materials for the adsorption of gases, 1416 as storage materials for various molecules, 1719 as potential candidates for targeted drug delivery 20,21 and for the encapsulation of biologically important molecules such as the DNA. 22,23…”
Section: Introductionmentioning
confidence: 99%